EMBRAPA 21: a new wheat cultivar recommended to the Brazilian States of Minas Gerais, Goiás, Mato Grosso and Federal District - Andrade, José Maria Vilela de; Albrecht, Julio César; Sousa, Cantídio N. A. de; Braz, Antônio Joaquim B. P.; Souza, Moacil Alves de (Pesquisa Agropecuaria Brasileira, 1998)
In a joint research program the Embrapa-Centro de Pesquisa Agropecuária dos Cerrados (CPAC), the Embrapa-Centro Nacional de Pesquisa de Trigo (CNPT), the Empresa de Pesquisa Agropecuária de Minas Gerais, the Empresa Goiana de Pesquisa Agropecuária (EMGOPA) and the Cooperativa Agropecuária Mista do Programa de Assentamento Dirigido do Alto Paranaíba (COOPADAP) developed a new cultivar - EMBRAPA 21 - for the States of Goiás, Minas Gerais, Mato Grosso and Federal District. The new cultivar is originated from crossings made in the International Center for Corn and Wheat Development, Mexico. It was introducted in Brazil through line colections and was identified in the trial of the Central Brazil research network as line CPAC 86133. The wheat cultivar Embrapa 21 is recommended for growing in non irrigated areas. It has medium qualities for the bread industry and is resistant to all races of stem and leaf rusts that occur in Brazil. In several experiments in different places and years, the yield of Embrapa 21 was 10% higher than the control BR 24 in Goiás and Federal District and 27% higher than the control BR 26-São Gotardo in Minas Gerais.